Review of Literature: The Clinical Nurses' Perception of Their Role in Hospital Reimbursement - McKinsey Patterson (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
Background: Nursing-sensitive indicators (NSI’s) serve to measure the impact nurses have in promotion of quality care. Existing research highlights the value-based purchasing (VBP) system implemented by the Affordable Care Act (ACA). Few studies explore nurse perception. Method: This review provides a state-of-the-science addressing NSI’s regarding delivery of quality care, hospital assessment related to value-based purchasing and the role of patient satisfaction regarding nursing care in the reimbursement of hospitals. Existing data related to nurses’ roles in VBP reimbursement efforts is described. Results: A theme in the literature is that the HCAHPS (Hospital Consumer Assessment of Healthcare Providers and Systems) survey, accounting for 30% of the total performance score, impacts funds allocated by the ACA guided by patient satisfaction, thus nursing quality. A gap in the science exists in understanding nurses’ perceptions of their role in the process of hospital reimbursement. Future research should assess these perceptions of how their care impacts hospital reimbursement and healthcare costs.
Keywords: value-based purchasing; nursing-sensitive indicators; hospital reimbursement; quality care; nursing administration